2015
DOI: 10.3389/fphys.2015.00235
|View full text |Cite
|
Sign up to set email alerts
|

Functional aortic stiffness: role of CD4+ T lymphocytes

Abstract: The immune system is suggested to be essential in vascular remodeling and stiffening. To study the dependence upon lymphocytes in vascular stiffening, we compared an angiotensin II-model of vascular stiffening in normal C57BL/6J mice with lymphocyte-deficient RAG 1−/− mice and additionally characterized the component of vascular stiffness due to vasoconstriction vs. vascular remodeling. Chronic angiotensin II increased aortic pulse wave velocity, effective wall stiffness, and effective Young's modulus in C57BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Some studies have suggested that immune cells, particularly T lymphocytes, play an important role in hypertension-related vascular dysfunction. This dysfunction is primarily mediated by the infiltration of T lymphocytes into the vascular system [17][18][19][20]. A study by Youn et al found a marked and independent correlation between cytomegalovirus phosphoprotein 65 (pp65)-specific cluster of differentiation 8 positive (CD8 þ ) T-cell responses and arterial stiffness in hypertensive patients [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that immune cells, particularly T lymphocytes, play an important role in hypertension-related vascular dysfunction. This dysfunction is primarily mediated by the infiltration of T lymphocytes into the vascular system [17][18][19][20]. A study by Youn et al found a marked and independent correlation between cytomegalovirus phosphoprotein 65 (pp65)-specific cluster of differentiation 8 positive (CD8 þ ) T-cell responses and arterial stiffness in hypertensive patients [21].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence suggests that aberrant immune responses, particularly T-cell responses, are associated with vascular complications of hypertension [17][18][19][20][21][22], but the precise mechanisms remain unclear. Arterial stiffness is regarded as a key feature of vascular complications in essential hypertension.…”
mentioning
confidence: 99%
“…Studies have also shown that the less compliant proximal arteries reduce the pressure gradient of proximal arteries to distal arteries. This may cause increased pressure in the microcirculatory system, a condition that could be harmful to areas of the brain and kidneys [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Tregs-derived IL-35 had a protective effect on right ventricular systolic pressure and right ventricular dilation in mice with pulmonary hypertension (191). IL-2/JES6-1 complex intervention effectively induced splenic Tregs amplification five times and inhibited Ang II mediated aortic collagen remodeling and atherosclerosis (192).…”
Section: Hypertensionmentioning
confidence: 96%